Open Interval Path Synthesis Method of Spatial RRSS Mechanism based on Numerical Atlas - Xiaodong Li; Lei Li (Jixie chuandong)
The existing numerical atlas methods can not realize open interval path synthesis of spatial RRSS mechanism. A path synthesis method of spatial RRSS mechanism is proposeed based on wavelet decomposition theory. By transforming path synthesis problem into the matching and identification problem of the basic types of mechanism，and the calculation problem of the actual sizes of mechanism，the open interval path synthesis of spatial RRSS mechanism is realized. Thus，it makes up for the deficiency of the numerical atlas method in solving the dimensional synthesis problem with open interval design requirements. A numerical example is presented to demonstrate the practicability and effectiveness of the proposed method.